Models of Pensions and Income Inequality: A Comparative Analysis - Joakim Palme (Luxembourg Income Study (LIS), 1989)
This paper studies if and how welfare state differences in old-age pensions affect various aspects of income inequality among the elderly in nine LIS countries.
Keywords: 330